Determinants of Nutritional Status among Toddlers in the Baduy Indigenous Community, Lebak Regency, Banten - Naomi Isabella Hutabarat; Suparmi (Miracle Journal Get Press, 2025)
Nutritional issues among toddlers remain a major public health concern, especially in indigenous communities with limited access to basic services and unique socio-cultural systems, such as the Baduy tribe in Banten, Indonesia. This study aimed to identify key determinants of toddler nutritional status in the Baduy community using a cross-sectional design and multivariate logistic regression analysis. A total of 120 toddlers aged 0–59 months from Baduy Dalam and Baduy Luar were purposively selected. Data were collected through anthropometric measurements and structured interviews covering demographic, economic, environmental, and healthcare access variables. Bivariate analysis (Chi-square) showed significant associations between nutritional status and maternal education, household economic status, environmental sanitation, and healthcare access (p < 0.05). Multivariate analysis confirmed these as significant predictors: low maternal education (AOR = 2.31), low economic status (AOR = 4.85), poor sanitation (AOR = 2.70), and limited healthcare access (>3 km) (AOR = 2.40). Child age and gender were not significant factors. The findings indicate that nutritional vulnerability in the Baduy is shaped by structural determinants tied to cultural norms, geographic isolation, and subsistence lifestyles. Effective interventions must be culturally sensitive, improve sanitation and food security, and ensure accessible, community-accepted health services, involving traditional leaders for sustainable impact.